2020
DOI: 10.1186/s13065-020-00721-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of oxadiazole or furadiazole containing compounds

Abstract: As we know that, Oxadiazole or furadi azole ring containing derivatives are an important class of heterocyclic compounds. A heterocyclic five-membered ring that possesses two carbons, one oxygen atom, two nitrogen atoms, and two double bonds is known as oxadiazole. They are derived from furan by the replacement of two methylene groups (= CH) with two nitrogen (-N =) atoms. The aromaticity was reduced with the replacement of these groups in the furan ring to such an extent that it shows conjugated diene charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…Moreover, it was reported that 1,3,4-oxadiazole scaffold has been found to be a potent antioxidant pharmacophore, and chemical modulation of the conventional drugs with this scaffold resulted in a synergistic effect, enhancing the antioxidant efficiency of the parent drug [47,49,50,83,84]. In our research, the presence of 1,3,4-oxadiazole scaffold significantly enhanced antioxidant activity for the majority of the NO-IND-OXDs.…”
Section: In Vitro Radical Scavenging Assaysupporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, it was reported that 1,3,4-oxadiazole scaffold has been found to be a potent antioxidant pharmacophore, and chemical modulation of the conventional drugs with this scaffold resulted in a synergistic effect, enhancing the antioxidant efficiency of the parent drug [47,49,50,83,84]. In our research, the presence of 1,3,4-oxadiazole scaffold significantly enhanced antioxidant activity for the majority of the NO-IND-OXDs.…”
Section: In Vitro Radical Scavenging Assaysupporting
confidence: 51%
“…On the other hand, the oxadiazole scaffold serves as core for many synthetic compounds of great interest in medicinal chemistry [47][48][49]. Its use offers several advantages: (i) it is an essential part of the pharmacophore, based on its ligand binding role; (ii) it acts as a flat aromatic linker assuring an appropriate molecule orientation; (iii) it induces metabolic stability, water solubility and lower lipophilicity; (iv) it can easily chemically modulate the compounds which contain carbonyl groups such as amides, carbamates, esters and hydoxamic esters [32,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Besides α -amylase inhibition, 1,3,4-oxadizole-based compounds have been found in commercially available drugs such as raltegravir as an antiviral agent, furamizole as an antibacterial agent, nesapidil as an antiarrhythmic agent and tiodazosin as an antihypertensive agent 35 . The structures of commercial drugs are shown in ( Figure 1(b) ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxadiazoles are five-membered heterocyclic compounds containing two nitrogen atoms and one oxygen atom in their structure. We can distinguish several isomeric forms of oxadiazole, which occur in the structure of many drugs, e.g., anticancer zibotentan [5], antimicrobial furamizole [6], antiviral raltegravir [7], ataluren for Duchenne muscular dystrophy [8] and others (Figure 1).…”
Section: Introductionmentioning
confidence: 99%